Gender Differences in Prevalence and Patterns of Dietary Supplement Use in Elite Athletes - Aguilar-Navarro, Millán; Baltazar-Martins, Gabriel; Brito de Souza, Diego; Muñoz-Guerra, Jesús; del Mar Plata, María; Del Coso, Juan (Research quarterly for exercise and sport, 2021)
Purpose: Dietary supplement use by athletes has been the topic of previous research; however, the lack of homogeneity among published studies makes it difficult to analyze the differences, if any, in the patterns of use between male and female athletes. The aim of this study was to determine gender differences in the patterns of dietary supplement use by elite athletes. Methods: A total of 504 elite athletes (329 males and 175 females) participating in individual and team sports completed a validated questionnaire on dietary supplement use during the preceding season. The dietary supplements were categorized according to the latest IOC consensus statement. Results: A higher proportion of male versus female athletes (65.3 versus 56.5%, p < .05) consumed dietary supplements. Both male and female athletes reported a similar mean consumption of dietary supplements (3.2 ± 2.1 versus 3.4 ± 2.3 supplements/season, respectively; p = .45). Protein supplements were the most commonly consumed supplements in male athletes (49.8%) and their prevalence was higher than in female athletes (29.3%, p < .01). In females, multivitamins (39.4%) and branched-chain amino acids (39.4%) were the most commonly consumed supplements and iron supplementation was more prevalent than in males (22.2% versus 10.2%, p = .01). A higher proportion of male athletes relied on themselves to plan dietary supplements use (48.0%), while female appeared to rely more on doctors (34.0%, p < .01). Conclusion: In summary, male athletes had a slightly higher prevalence in the use of supplements than their female counterparts, specifically regarding protein supplements, and were more involved in the self-prescription of supplements.